Trading strategies for capital markets - Benning, Joseph F (McGraw-Hill, 2007)
Trading Strategies for Capital Markets is a comprehensive guide that shows how capital markets work in the real world, fully exploring price drivers, major players, key elements of the securities and derivatives traded, and ways of devising on-target trading strategies.